Determination of the Energetic Needs of Low Energy Housing and Integration of a Solar Water Heating Installation Located in Algeria. (August 2015) - Sami-Mecheri, S.; Semmar, D.; Hamid, A.
Abstract: In the present article, we present a numerical simulation (winter and summer) of a low energy housing of 70 m 2 surface area in Algiers region. This region is part of the climate zone, A which is characterized by a cool winter and hot and humid summer. In our simulation, we use the Pleiades and Comfie software. In Order to see the temperature variation of the comfort zone; we illustrate our simulations for two weeks, the hottest and coldest week of the year. To know the energy needs (heating and cooling) we run a simulation with the thermostat instructions (the comfort temperature must be between 20° C and 24° C).we take into account different scenarios: the occupancy, the ventilation, the occupation and the dissipated energy. Note that the external temperatures injected are measured values. We integrate also in the study a solar water heating system, the simulation is done with solo software developed by Tecsol. The results shows clearly that the comfort is attended in summer, but not quite in winter and the good efficiency of water heating installation.